Epigallocatechin Gallate Induces the Demethylation of Actinin Alpha 4 to Inhibit Diabetic Nephropathy Renal Fibrosis via the NF-KB Signaling Pathway In Vitro - Chunling He; Dong Wang; Ruoling Wang; Yongli Huang; Xin Huang; ShuMin Shen; Jun Lv; Mingcai Wu (SAGE Publishing, 2022)
Actinin alpha 4 ( ACTN4 ) is expressed in the kidney podocytes. ACTN4 gene methylation in patients with diabetic nephropathy (DN) remains high. Underlying mechanism of epigallocatechin-3-gallate (EGCG) inducing ACTN4 demethylation, and its inhibitory effect on DN renal fibrosis remains unclear. Methods: Human podocyte cell line, HPC, was treated with high glucose to establish model of DN. The levels of cytokines, vascular endothelial growth factor (VEGF) and interleukin (IL)-8, and fibrosis markers, alpha smooth muscle actin (α-SMA) and fibronectin (FN), were determined using enzyme-linked immunosorbent assay. HPC cells were treated with EGCG, and cell viability was determined by MTT assay, ACTN4 gene methylation was analyzed by MSP. mRNA and protein expression levels were measured using RT-qPCR and Western blotting, respectively. Results: Actinin alpha 4 gene promoter was hypermethylated in the high glucose-treated groups. EGCG reversed the hypermethylated status of ACTN4 , along with the upregulation of ACTN4 levels and downregulation of DNA methyltransferase 1 (DNMT1), NF-κB p65, p-NF-κB p65, IκB-α, VEGF, IL-8, α-SMA, and FN levels ( P <.05). Conclusion: Epigallocatechin-3-gallate reduced hypermethylation of ACTN4 in HPC cells by downregulating DNMT1 expression and restoring ACTN4 expression, contributing to the upregulation of the NF-KB p65, p-NF-KB p65, IKB-α, VEGF, IL-8, α-SMA, and FN levels (P<.05).